Impaired Subjective Visual Vertical and Increased Visual Dependence in Older Adults With Falls - Totilienė, Milda; Uloza, Virgilijus; Lesauskaitė, Vita; Damulevičienė, Gytė; Kregždytė, Rima; Kaski, Diego; Ulozienė, Ingrida (Frontiers in Aging Neuroscience, 2021)
Ageing affects the vestibular system and may disturb the perception of verticality and lead to increased visual dependence (VD). Studies have identified that abnormal upright perception influences the risk of falling. The aim of our study was to evaluate subjective visual vertical (SVV) and VD using a mobile virtual reality-based system for SVV assessment (VIRVEST) in older adults with falls and evaluate its relationship with clinical balance assessment tools, dizziness, mental state and depression level. This study included 37 adults >65 years who experienced falls and 40 non-faller age-matched controls. Three tests were performed using the VIRVEST system: a static SVV, dynamic SVV with clockwise and counter-clockwise background stimulus motion. VD was calculated as the mean of absolute values of the rod tilt from each trial of dynamic SVV minus the mean static SVV rod tilt. Older adults who experienced falls manifested significantly larger biases in static SVV (p=0.012), dynamic SVV (p<0.001), and VD (p=0.014) than controls and had a greater risk for falls. The increase in static SVV (odds ratio=1.365, p=0.023), dynamic SVV (odds ratio=1.623, p<0.001) and VD (odds ratio=1.460, p=0.010) tilt by one degree significantly related to falls risk in the faller group. Fallers who had a high risk of falling according to the Tinetti test, exhibited significantly higher tilts of dynamic SVV than those who had a low or medium risk (p=0.037). In the faller group, the increase of the dynamic SVV tilt by one degree was significantly related with falls risk according to the Tinetti test (odds ratio=1.356, p=0.049). SVV errors, particularly with the dynamic SVV test (i.e., greater VD) were associated with increased risk of falling in the faller group. The VIRVEST system may be applicable in clinical settings for SVV testing and predicting falls in older adults.